2019
DOI: 10.14336/ad.2019.0208
|View full text |Cite
|
Sign up to set email alerts
|

The Long-lasting Radioprotective Effect of Caffeic Acid in Mice Exposed to Total Body Irradiation by Modulating Reactive Oxygen Species Generation and Hematopoietic Stem Cell Senescence-Accompanied Long-term Residual Bone Marrow Injury

Abstract: Total body irradiation (TBI) serves as an effectively curative therapy for cancer patients and adversely causes long-term residual bone marrow (BM) injury with premature senescence of hematopoietic stem cells (HSCs), which is mediated by increased production of reactive oxygen species (ROS). In the present study, we investigated how the exposure time of TBI in a mouse model affects HSCs and whether the treatment of caffeic acid (CA), a known dietary phenolic antioxidant, has a radioprotective effect. Single (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Taken as a whole, it is suggested that NRF2 is a potential therapeutic target to ameliorate or prevent TBI-mediated oxidative injuries, as well as to regulate self-renewal, proliferation, and differentiation of stem cells [ 43 ]. Overall, our current findings with previous reports [ 9 , 24 ] strongly suggest that the ferulic-acid-induced radioprotection is closely associated with the enhanced or maintained antioxidant defense systems that are followed by NRF2 upregulation.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Taken as a whole, it is suggested that NRF2 is a potential therapeutic target to ameliorate or prevent TBI-mediated oxidative injuries, as well as to regulate self-renewal, proliferation, and differentiation of stem cells [ 43 ]. Overall, our current findings with previous reports [ 9 , 24 ] strongly suggest that the ferulic-acid-induced radioprotection is closely associated with the enhanced or maintained antioxidant defense systems that are followed by NRF2 upregulation.…”
Section: Discussionsupporting
confidence: 88%
“…Although therapeutic radiation can cause severe damages to intact soft and hard tissues [ 20 , 21 ], TBI is required for cancer patients or in BM transplantation. Reduced bone mass accrual and BMD, increased ROS and oxidative stress, long-term residual BM injury, and stem cell senescence with the attendant hematopoietic defects are to be the hallmarks of TBI-mediated disorders [ 9 , 22 , 23 , 24 ]. Disruption of cellular redox balance and depletion of endogenous antioxidant defense systems are also the main events in TBI-mediated oxidative damages [ 9 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations